An Ecological and Taxonomic Study of Freshwater Molluscs near Alkabo River Estuary, Lattakia – Syria. - ياسين قصاب محمد; فاضل اقبال; حسن ديما (Latakia University Journal -Biological Sciences Series, 2021)
Among several station in the AlKabo River, one station close to the estuary was selected to conduct environmental and taxonomic studies, in addition to performing an inventory for the freshwater mollusks that live in the area during the period from 07/10/2016 to 27/10/2017. Samples were collected twice a month during spring, summer and autumn and once a month during winter. Nine species of mollusks have been identified, all belonging to the class of Gastropoda (four species from the sub class Prosobranchia, and five others from the sub class Pulmonata). The species Hydrobia ventrosa was recorded for the first time in Latakia Governorate, and the degree of species stability and their relative frequency were determined. The physical and chemical characteristics of the water in the aforementioned station have been determined. It has been found that the water is of a stinging nature, and an increase in the values ​​of chlorine ions and BOD has been observed in summer and autumn, which reflects the presence of organic pollution of anthropogenic origin (sewage) in this period of the year.